2019
DOI: 10.1111/joss.12550
|View full text |Cite
|
Sign up to set email alerts
|

Sensory sensitivity to sour and bitter taste among people with Crohn's disease and folic acid supplementation

Abstract: The aim of the study was to compare differences between healthy young people and young people with Crohn's disease in their sensory sensitivity to basic tastes. The investigations were conducted on a group of 185 people with Crohn's disease and 288 healthy people aged 20-31. The recognition thresholds of sweet, salty, sour, and bitter tastes were determined. The results showed that the young people with Crohn's disease were more sensitive to sour taste and less sensitive to bitter taste than the healthy subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Our study shows that some of the spice ethanol extracts are carriers of the bitter taste, and this can decrease the overall desirability of pork meatballs and hamburgers. Consumers can rate overall palatability without being consciously aware of all food ingredients, especially those present at near-threshold levels [54,55] which are characteristic for individuals [56]. For this reason, the masking of bitterness can be crucial in the development of new products with spice addition.…”
Section: Discussionmentioning
confidence: 99%
“…Our study shows that some of the spice ethanol extracts are carriers of the bitter taste, and this can decrease the overall desirability of pork meatballs and hamburgers. Consumers can rate overall palatability without being consciously aware of all food ingredients, especially those present at near-threshold levels [54,55] which are characteristic for individuals [56]. For this reason, the masking of bitterness can be crucial in the development of new products with spice addition.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by previous studies indicating low acceptance of this descriptor among consumers. Previous studies also revealed that bitter taste can reduce consumer acceptance of food products [60][61][62][63]. The highest statistically significant taste and overall desirability were found among the samples with lovage regardless of the addition of legume seeds.…”
Section: Discussionmentioning
confidence: 81%
“…Significant factors include the perception of powdered and metallic tastes. Earlier studies have shown that bitter taste can decrease consumer acceptance of food products, particularly those for which this taste is not characteristic [ 33 , 34 , 35 ]. Additionally, metallic taste is an important problem in food technology, for example, with sweeteners.…”
Section: Resultsmentioning
confidence: 99%